2020
DOI: 10.1109/jsen.2020.2987007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Initial Stage of Aluminum Corrosion in NaCl Solution Utilizing Surface Plasmon Resonance

Abstract: Surface plasmon resonance (SPR) spectra on Al films in the Kretschmann configuration is investigated aiming at the rapid detection of the Al corrosion in NaCl solution. The angle of the dip, occurred in the SPR spectra, was observed to decrease in the first 20 min and then increase with the increase of the immersion time. Calculations based on a simple multilayer model suggest that the observed initial decrease and the subsequent increase in the dip angle correspond to the thinning of the oxide layer and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They concluded that the grating configuration makes it possible to obtain more robust electrodes for coupled plasmonic and electrochemical measurements, plus to overcome the problems encountered with both the Otto and Kretschmann-Raether configurations. Kosako et al 11 focused on detecting the initial stage of aluminum pitting corrosion in 3 wt% NaCl solution using SPR with the Kretschmann-Raether configuration. These authors investigated modifications in the thickness of the aluminum layer consumed during exposure of the metal with chloride ions without any applied potential.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the grating configuration makes it possible to obtain more robust electrodes for coupled plasmonic and electrochemical measurements, plus to overcome the problems encountered with both the Otto and Kretschmann-Raether configurations. Kosako et al 11 focused on detecting the initial stage of aluminum pitting corrosion in 3 wt% NaCl solution using SPR with the Kretschmann-Raether configuration. These authors investigated modifications in the thickness of the aluminum layer consumed during exposure of the metal with chloride ions without any applied potential.…”
Section: Introductionmentioning
confidence: 99%